Public acceptance of carbon tax implementation: a nationwide empirical study in Malaysia - Izlawanie Muhammad,; Norfakhirah Nazihah Mohd Hasnu,; Mohd Adha Ibrahim,; Suhaila Abdul Hamid,; Mustafa Mohd Hanefah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study investigates public personal traits and demographic factors influencing their acceptance of the implementation of carbon tax policy in Malaysia. Understanding the public's acceptance behaviour becomes crucial as carbon tax gains attention in developing countries. Through an online survey of 566 respondents, the research employs multiple regression analysis, t-test and one-way analysis of variance to examine the relationships. The results indicate that the carbon tax policy receives positive support from the public, who perceive carbon tax as an effective policy to reduce carbon emissions, those willing to pay more to protect the environment, those who recognise climate change as a serious issue and the Chinese community. These findings fill a gap in the environmental taxation literature for developing countries, offering insights for the Malaysian government to formulate effective strategies for public support. It is imperative for the government to consistently disseminate information to the public and create awareness through mass media regarding the serious issue of climate change and the effectiveness of a carbon tax to mitigate it. Regardless of the political party in power, adopting a carbon tax should be prioritised as a national agenda to maintain the country's economic, social, and environmental sustainability to demonstrate the government's unwavering commitment.